JENIS-JENIS IKAN SEGAR YANG DIPERDAGANGKAN DI PASAR MODERN KABUPATEN ROKAN HULU PROVINSI RIAU - -, Realita; Ade, Filza Yulina; -, Dahlia (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about the diversity of fresh fish that sold in Modern Market Rokan Hulu Regency Riau Privince has been conducted in December 2014 to Januari 2015 by using survey method. Result showed 24 species of fresh fish were found, they were Caesio caerulaurea, C. cuning, Caranx rotteri, Channa striata, C. Micropeltes, Clarias gariepinus, C. batrachus, Cyprinus carpio, Elagatis bipinnulata, Euthynnus affinis, Hampala macrolepidota, Lutjanus sanguineus, Mastacembelus erythrotaenia, Monopterus albus, Mystus nemurus, Ompok hypophthalmus, Oreochromis niloticus, Osphronemus gouramy, Pangasius pangasius, Pristolepis grooti, Rasbora caudimaculata, Rastrelliger kanagurta, Thynnichthys polylepis and Wallago leeri